2015
DOI: 10.1016/j.jes.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and molecular dynamic simulation study of perfluorooctane sulfonate adsorption on soil and sediment components

Abstract: Soil and sediment play a crucial role in the fate and transport of perfluorooctane sulfonate (PFOS) in the environment. However, the molecular mechanisms of major soil/sediment components on PFOS adsorption remain unclear. This study experimentally isolated three major components in soil/sediment: humin/kerogen, humic/fulvic acid (HA/FA), and inorganic component after removing organics, and explored their contributions to PFOS adsorption using batch adsorption experiments and molecular dynamic simulations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…It is notable that while Vinton soil has a very low organic-carbon content, it has by far the largest metal-oxide content. The greater proportion of oxides likely supports adsorption via additional mechanisms beyond hydrophobic interaction, such as electrostatic interactions and the formation of complexes by ligand exchange with metal oxides, as has been observed in prior studies for PFAS and hydrocarbon surfactants. This additional adsorption is lumped into the log K oc value. A similar observation of greater adsorption by Vinton compared to Eustis soil was reported for PFOS …”
Section: Resultsmentioning
confidence: 87%
“…It is notable that while Vinton soil has a very low organic-carbon content, it has by far the largest metal-oxide content. The greater proportion of oxides likely supports adsorption via additional mechanisms beyond hydrophobic interaction, such as electrostatic interactions and the formation of complexes by ligand exchange with metal oxides, as has been observed in prior studies for PFAS and hydrocarbon surfactants. This additional adsorption is lumped into the log K oc value. A similar observation of greater adsorption by Vinton compared to Eustis soil was reported for PFOS …”
Section: Resultsmentioning
confidence: 87%
“…Research investigating PFAS adsorption by solids has become a focus over the past decade, with investigations examining water treatment applications (as reviewed in Du et al, 2014 and Merino et al, 2016) and subsurface porous media--- soils and sediments (Liu and Lee, 2005, 2007, Higgins and Luthy, 2006, 2007, Johnson et al, 2007, Carmosini and Lee, 2008, Chen et al, 2009, Pan et al, 2009, Ferrey et al, 2012, Guelfo and Higgins, 2013, Zhao et al, 2014, Milinovic et al, 2015, Zhang et al, 2015, Hellsing et al, 2016). Adsorption of PFAS by solids is complex due to the nature of the molecular structure of PFAS.…”
Section: Evaluation Of Retention Processesmentioning
confidence: 99%
“…As would be anticipated, research has shown that PFAS sorption by subsurface media is greatly affected by the geochemical properties of the solid, particularly with respect to specific components present. Critical factors investigated for PFAS include the magnitude and nature of organic carbon, magnitude and type of metal oxides, and clay mineralogy (Higgins and Luthy, 2006, Liu and Lee, 2007, Ferrey et al, 2012, Milinovic et al, 2015, Zhang et al, 2015). In addition, it is well known that the adsorption of surfactants is sensitive to water chemistry.…”
Section: Evaluation Of Retention Processesmentioning
confidence: 99%
“…we previously characterized adsorption on pristine smectite using MD simulations. Other previous atomistic simulation studies of the adsorption of similar contaminants on organic-coated minerals have modeled PFAS adsorption on organic-coated silica surfaces and within an organic-coated Na-smectite nanopore, but these studies simulated very short time scales (2.1 ns or less) and did not quantify the free energy of adsorption of the organic contaminant (Yan et al, 2020;R. Zhang et al, 2015).…”
Section: Core Ideasmentioning
confidence: 99%
“…We focus on two contaminants, dimethyl phthalate (DMP), an uncharged polar chemical plasticizer, and perfluorobutanesulfonic acid (PFBS), a short chained anionic surfactant in the family of per‐ and polyfluoroalkyl substances (PFAS), for which we previously characterized adsorption on pristine smectite using MD simulations. Other previous atomistic simulation studies of the adsorption of similar contaminants on organic‐coated minerals have modeled PFAS adsorption on organic‐coated silica surfaces and within an organic‐coated Na‐smectite nanopore, but these studies simulated very short time scales (2.1 ns or less) and did not quantify the free energy of adsorption of the organic contaminant (Yan et al., 2020; R. Zhang et al., 2015). Previous experimental studies have observed significantly enhanced adsorption of perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) on smectite clay in the presence of cationic surfactants such as hexadecyltrimethylammonium bromide (Tian et al., 2016; Zhou et al., 2010), whereas humic acid, tannic acid, and Suwannee River natural organic matter coatings resulted in decreased PFOS and PFOA adsorption compared with pure smectite surfaces (Jeon et al., 2011).…”
Section: Introductionmentioning
confidence: 99%